Controls on the Cadmium‐Phosphate Relationship in the Tropical South Pacific. Issue 10 (20th October 2017) - Roshan, Saeed; Wu, Jingfeng; DeVries, Timothy
Abstract: The relationship between dissolved cadmium (Cd) and phosphate (PO4 −3 ) can elucidate a biological role for Cd in the ocean and help to evaluate the usefulness of Cd as a tracer of past ocean circulation and nutrient distributions. Here we determine and analyze this relationship in the poorly studied region of the tropical South Pacific. The dissolved Cd distribution is generally similar to PO4 3−, but a plot of Cd versus PO4 3− shows a clear concavity resulting from distinct Cd:PO4 3− ratios in waters local to our transect and in waters formed distally in higher latitudes. To determine the factors affecting the subsurface Cd:PO4 3− ratio along our transect, we used an ocean circulation model and a multilinear regression model to determine the preformed and regenerated components of dissolved Cd and PO4 3− . We found that both the preformed and regenerated Cd:PO4 3− ratios are low in the shallow, locally formed water masses along the transect and significantly higher in the deeper and older water masses. Overall, the regenerated:preformed Cd:PO4 3− ratio in the deep waters (>1, 000 m) along our transect is 1.8:1, reflecting the basin‐wide average Cd:PO4 3− "fractionation factor" during biological uptake. However, we find a lower fractionation factor in local waters of 1.1 (± 0.6). We suggest that this locally lower biological fractionation factor is due to either the chemical speciation of Cd or to a lower efficiency of Cd assimilation by the picoplankton and nanoplankton species found in our study region. Key Points: Dissolved Cd and PO4 3− show different correlations in the near‐surface and deep waters of the Eastern Tropical Pacific The Cd:PO4 3− regenerated:preformed ratio is 1.8(plus/minus 0.06):1 in the deep Eastern Tropical Pacific but 1.1(plus/minus 0.6):1 above 250 m Differences between shallow and deep regenerated:preformed Cd:PO4 3− ratios may be explained by Cd speciation or plankton Cd requirements